DOI: 10.14264/uql.2014.449
|View full text |Cite
|
Sign up to set email alerts
|

Newborn EEG connectivity analysis using time-frequency signal processing techniques

Abstract: Scalp electroencephalography (EEG) monitoring in early life is providing vital assistance to clinical management during diagnosis and treatment of developing brain disorders. It is also a useful tool for predicting long-term neurological outcomes of perinatal injuries. Continuous evolution of cerebral structures during early brain maturation imposes salient changes in the temporal morphology of newborn EEG patterns. Therefore, dealing with neonatal EEG signals is technically very challenging. The current domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 169 publications
(337 reference statements)
0
4
0
Order By: Relevance
“…Connectivity studies have shown that long range connections within the brain of the newborn develop much quicker than short range cortical connections, thus making unilateral autonomous cortical activity in newborn babies to be dominant, with no substantial interhemispheric relationship noted at this point [32] . In the first few months, expansion of neuronal pathways occur, which give rise to dynamic changes in the EEG waveform in due course [32] .…”
Section: Seizure Eeg Waveform Theoretical Representation and Newborn ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Connectivity studies have shown that long range connections within the brain of the newborn develop much quicker than short range cortical connections, thus making unilateral autonomous cortical activity in newborn babies to be dominant, with no substantial interhemispheric relationship noted at this point [32] . In the first few months, expansion of neuronal pathways occur, which give rise to dynamic changes in the EEG waveform in due course [32] .…”
Section: Seizure Eeg Waveform Theoretical Representation and Newborn ...mentioning
confidence: 99%
“…Connectivity studies have shown that long range connections within the brain of the newborn develop much quicker than short range cortical connections, thus making unilateral autonomous cortical activity in newborn babies to be dominant, with no substantial interhemispheric relationship noted at this point [32] . In the first few months, expansion of neuronal pathways occur, which give rise to dynamic changes in the EEG waveform in due course [32] . The general dynamic characteristic of a newborn's EEG is intermittent and discontinuous activity alongside a mixture of bursts of spontaneous activity transients (SAT), and general low voltage activity, which is distinct from burst suppression activity that mostly appears in newborns with existing brain damage [32] .…”
Section: Seizure Eeg Waveform Theoretical Representation and Newborn ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The data preparation and the analysis were performed in MATLAB 2020b (Mathworks, Inc.). DTF was computed using MATLAB implementation (Omidvarnia, 2020;Omidvarnia et al, 2011). Vector autoregression coefficients were computed using the ARFIT package (Neumaier and Schneider, 2001).…”
Section: Softwarementioning
confidence: 99%